The assembly history of disc galaxies - Miller, S (2013)
We present new measures of the rotation curves of disc galaxies from z~0.2 to z~1.7, using deep exposures from both DEIMOS and LRIS spectrographs on the Keck telescopes in combination with multi-band imaging from the Hubble Space Telescope. We do this with a new modelling code, curvation, which has been optimised to extract the rotation velocity measurements from galaxies at intermediate and high redshift. To this end, we conduct a bulge-to-disc de-composition to allow us to de-project observed velocities to extract a model of the intrinsic rotation curve. We demonstrate the improved accuracy and precision of these measurements via a number of tests, but primarily in recovering an intrinsic scatter of the high redshift Tully-Fisher relation which is similar to that found locally. We show for the first time that the stellar mass Tully-Fisher relation is tightly in place at z~1, the normalisation of which has evolved less than 0.02±0.02 dex in stellar mass from z~1.7 to z~0.2. We do however see evidence for evolution in classic B-band Tully-Fisher relation, which is brighter at z~1 by 0.85±0.28 magnitudes than that at z~0.3. This trend is consistent with what was previously known about the evolving star-formation rates of disc galaxies. We then explore the potential drivers of these trends in the Tully-Fisher relation by estimating the baryonic and dark matter content of our galaxies. We also discover a surprising trend in the bulgeless disc galaxies at high redshift, which may be evolving differently from other rotationally supported galaxies. In the context of work which has been conducted at z~2, we discuss our results of a stellar mass Tully-Fisher relation which is strikingly similar over two-thirds of the age of the Universe.